Effects of pelvis-shoulders torsional separation style on kinematic sequence in golf driving. Issue 6 (2nd November 2019) - Han, Ki Hoon; Como, Christopher; Kim, Jemin; Hung, Cheng-Ju; Hasan, Mohammad; Kwon, Young-Hoo
ABSTRACT: The golfer's body (trunk/arms/club) can be modeled as an inclined axle-chain system and the rotations of its parts observed on the functional swing plane (FSP) can represent the actual angular motions closely. The purpose of this study was to investigate the effects of pelvis-shoulders torsional separation style on the kinematic sequences employed by the axle-chain system in golf driving. Seventy-four male skilled golfers (handicap ≤ 3) were assigned to five groups based on their shoulder girdle motion and X-factor stretch characteristics: Late Shoulder Acceleration, Large Downswing Stretch, Large Backswing Stretch, Medium Total Stretch, and Small Total Stretch. Swing trials were captured by an optical system and the hip-line, thorax, shoulder-line, upper-lever, club, and wrist angular positions/velocities were calculated on the FSP. Kinematic sequences were established based on the timings of the peak angular velocities (backswing and downswing sequences) and the backswing-to-downswing transition time points (transition sequence). The backswing and transition sequences were somewhat consistent across the groups, showing full or partial proximal-to-distal sequences with minor variations. The downswing sequence was inconsistent across the groups and the angular velocity peaks of the body segments were not significantly separated. Various swing characteristics associated with the separation styles influenced the motion sequences.